KAJIAN PENGEMBANGAN ILMU TAUHID/KALAM - Mulyono, Mulyono (ULUL ALBAB Jurnal Studi Islam, 2009)
Learning Sciences Tauhid / Kalam became a problem faced by all educators of Islam, both within schools, madrasah, Islamic schools, the board taklim to the college environment. Because the problems discussed in monotheism itself is the abstract / invisible. Therefore, educators should use different approaches in the assessment and development Science of Tauhid/Kalam, including: (1) theological approach (naqli), (2) a philosophical approach (aqli), (3) theoretical approach, and (4) contextual approach and applicative. The learning strategies that can be used to achieve competency standards students, can be done through: (1) The models of innovative learning, (2) Use the maximum learning media, (3) Assessment of the proportion from the beginning until the end of the lesson, (4) Materials Science of Tauhid should be linked to other sciences related to and supportive.